PERENCANAAN PERBAIKAN SUNGAI BABON KOTA SEMARANG - Bramantyo Yuda Perdana; Setyo Bagus Panuntun; Sumbogo Pranoto; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Flooding is a situation where areas not normally inundated with water becomes stagnant. And very adverse circumstances moriil both material as well as inhibition of transport impact on the rate of the economy of a region. Flooding problems that occurred in the city of Semarang is partly due to overflowing, one of the river is the river layer. Babon river have a length of about 17 km starting from Pucang Gading Dam downstream to the estuary through Karang Roto Dam. Babon river conditions experienced narrowing and shallowing flow leads to reduced capacity to cross the river flood discharge flow. Babon river can no longer accommodate the flood discharge that occurs especially in the rainy season so that commemorate the area around the river layer. In addition, the floods also caused the creek bank that opened for the access road so the water from the river could easily overflow. From studies and calculations have been done, solving this problem is to conduct repairs on the Babon River, by improving the flow and cross the river and make retrofitting Babon River on slopes / riverbanks prone to landslides. So as to reduce the level of flooding in the city of Semarang.